What is the Level of Self-Directed Learning among Junior High School Students? - Hilda Hidayatun Nafi’ah; Caraka Putra Bhakti (Universitas Negeri Semarang, 2025)
This study aims to describe the level of Self-Directed Learning skills of students at SMP Negeri 3 Banguntapan. Self-Directed Learning is an important skill that enables students to learn independently, take the initiative in understanding the material, and develop effective learning strategies. The research method used was a descriptive survey with a sample of 224 students, selected using accidental sampling techniques. Data collection used the Self-Directed Learning scale adapted from Henisa and Restu Aulia Chairunnisa. This scale consists of 30 items with five indicators: awareness, learning strategies, learning activities, evaluation, and interpersonal skills. The analysis results showed an average Self-Directed Learning score of 75 (SD = 15). A total of 9% of students had Self-Directed Learning skills, 70% were in the moderate category, and 21% were classified as low. These findings indicate that the majority of students still need reinforcement in Self-Directed Learning skills. Factors contributing to low Self-Directed Learning include conventional learning methods, lack of opportunities for students to learn independently, and an education system that is still dominated by a top-down approach. Therefore, innovation in guidance and counseling services is needed to improve Self-Directed Learning skills, so that students can be better prepared to face challenges in education and work.